Helen Keller und die linguistische Aufhebung des aristotelischen „Anfangs“ - Gutberlet, Albert (Alpha omega, 2019)
Philosophy in the Aristotelian sense may currently appear to have been replacedby the pragmatic sciences. But while today Aristotle’s justification of philosophy based on the “natural desire to know” seems insufficient, Helen Keller’s life and writings offer us anew ground for continuing in the Aristotelian Tradition: the “natural desire to communicate”, which “sublevates” or “takes up” the cognitive desire without discarding it.